The Implementation of Insolvency Test on Debtors’ Bankruptcy in Performing the Principle of Justice - Ikhwansyah, Isis; Sidabutar, Lambok Marisi Jakobus (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2019)
Bankruptcy requirements as a legal basis for bankruptcy applications are only based on the burden of proof in a simple manner which results in the debtor being easily declared bankrupt by the court. This impedes the realization of the principle of justice that has been mandated in Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (SDPO). This article aims to analyze the basis of justice related to the bankruptcy of the debtor and the implementation of the bankruptcy test in relation to the request for bankruptcy submitted to the debtor. This study is a normative juridical research method that uses descriptive-analytic research. This study also uses library research to collect data andÂ analyzes data with qualitative juridical methods. The results show that the debtor's bankruptcy application did not apply the Bankruptcy test. It is believed that insolvency testÂ on the debtor's bankruptcy petition is as a manifestation of the principle of justice that is in accordance with Pancasila by providing balanced protection among creditors, debtors and other stakeholders.